Risk factors for unsuccessful induction of labour at Mowbray Maternity Hospital - Mfutila, Tsitukenina Ruffine (Department of Obstetrics and Gynaecology, 2025)
BACKGROUND: Induction of labour (IOL) is a commonly performed obstetrical procedure. Over time, the rate of IOL has varied from region to region, with a progressive increase and almost doubling of the incidence in some developed countries.1 According to the World Health Organization (WHO), IOL may account for up to 25% of all term deliveries in developed countries and account for only 4.4% of deliveries on average in African countries.2 Major concerns associated with IOL are the potential for increased risk of emergency caesarean delivery (CD), iatrogenic prematurity and cost. The increasing IOL rates worldwide have resulted in debates on the cost benefit ratio of this procedure. There is no consensus on what constitutes unsuccessful IOL (USIOL). Some studies consider failure to achieve vaginal delivery as USIOL. Another view is that, since the purpose of IOL is to cause a non-labouring woman to go into labour, failure to achieve active labour should be the definition of USIOL. More accurate prediction of USIOL would provide useful information for the obstetrician and the women being counselled for IOL. For this study, unsuccessful IOL was defined as failure to achieve 5 cm cervical dilation (onsetof active labour) despite IOL methods. The main aim of this study was to identify factors associated with USIOL at the Mowbray Maternity Hospital (MMH), a regional referral hospital in Cape Town. METHODS: This was a retrospective observational study. We identified women undergoing IOL in MMH labour wards between 01/01/2019 and 31/03/2019 and reviewed their medical records. Women having IOL with preterm gestations less than 34 weeks, with intra-uterine fetal death, with multiple pregnancy and prior caesarean delivery were excluded. Data was collected on background factors, indications for IOL, obstetric factors and outcomes. It was hypothesised that hypertension as the indication for IOL would be a significant risk factor for USIOL, and a sample size of 240 was estimated to be appropriate. Ethics approval was obtained from the Human Research Ethics Committee of the faculty of Health Sciences of the University of Cape Town (UCT). RESULTS: Of the 240 women who commenced IOL during the study period, 223 were eligible for inclusion. SIOL (achieving active labour; ≥5 cm cervical dilatation) occurred for 169 (75.8%) women and USIOL occurred for 54 (24.2%). The study revealed two factors statistically associated with USIOL: nulliparity, and low birthweight. In the USIOL group, 51.9% were nulliparous compared to 33.1% of SIOL (p=0.013). In the USIOL group, 18.5% of babies weighed less than 2.5 kgms compared to 8.3% in SIOL (p=0.006). Hypertension as an indication for IOL, as hypothesised in the sample size estimation, was not a determinant for USIOL. The most frequent indications for IOL were Prolonged pregnancy (31.8%), Hypertension (26%), Pre-labour rupture of membranes (13.5%), and ‘Other' category (29%) which was a composite of several less common indications. There were no significant differences in IOL indications between SIOL and USIOL groups. The USIOL group had a higher proportion of IOLs performed that were late preterm (34 to 36+6 weeks) compared to SIOL which correlates with the significantly lower birthweight in this group. Body Mass Index of the total study population was ≥ 30 kgms/m² (obesity) for 134 women (60%), yet this study did not show an association between body mass index and USIOL (p=0.864). For the method of IOL, a higher proportion of the USIOL group had misoprostol (66.7%) compared to SIOL (58.6%); whereas a higher proportion of the SIOL group had intracervical catheter (40.2%) than the USIOL group (31.5%), but these differences were not statistically significant. The mean Induction to Delivery (I-D) intervals, was 18h43min for the whole study group; 18h19min for SIOL and 19h57min for USIOL. The caesarean delivery rate for the whole study group was 35%. By definition, it was 100% in the US IOL group. Of the 169 women with SIOL, 26 (15.4%) had emergency caesarean delivery, of which 46.1% were for an abnormal CTG, 34.6% for failure to progress into active labour, and 15.4% for an undiagnosed breech in labour. In the USIOL group, the majority of CD, 37 (68.5%) were performed for an abnormal CTG with only 14 (26%) being done for a truly failed IOL that did not progress into active labour despite receiving IOL methods. There were no major adverse maternal or perinatal outcomes in SIOL or USIOL groups, with 7 babies (3% of the whole study group) requiring admission to the neonatal unit. DISCUSSION AND CONCLUSION: The study revealed two factors statistically associated with USIOL: nulliparity, and low birthweight. The higher proportion of low birthweight babies in the USIOL group, suggests undetected intrauterine growth restriction that may have been associated with the higher rate of CTG abnormalities in this group requiring CD, and/or the non-significant increase in the proportion of late preterm gestations. Hypertension, as hypothesised in the sample size estimation was not a risk factor for USIOL. The majority of women with USIOL had CD for an abnormal CTG during the process of IOL, rather than failure to progress into active labour, related possibly to high-risk fetuses or the IOL method employed. Of note, the success rate for IOL was 75.8%, the overall CD rate of 35% in women commencing IOL was less than the average for MMH; and there were few maternal and perinatal complications. This information is valuable when counselling women for IOL at MMH.